GEODYNAMIC ACTIVITY OF THE LITHOSPHERE AND PROBLEMS OF TECTONOPHYSICS – OUTLOOK AFTER 35 YEARS - K. G. Levi (Геодинамика и тектонофизика, 2015)
Reviewed are aspects of modern geodynamics and methods of mapping of geodynamic processes which have been developed since 1960s in the Institute of the Earth's Crust, Siberian Branch of RAS (specifically since 1980s by the Laboratory of Tectonophysics and now jointly with the Laboratory of Recent Geodynamics). Achievements and prospects of the studies are discussed. The publication is devoted to the 35th anniversary of the Laboratory of Tectonophysics and its main achievements in geodynamics.